Comparison of triglyceride glucose index and HbA1C as a marker of prediabetes – A preliminary study. Issue 9 (September 2022) - Darshan AN, Venkatesh; Rajput, Rajesh; Meena,; Mohini,; Garg, Rakesh; Saini, Suyasha
Abstract: Background and aims: HbA1 C and HOMA-IR (Homeostatic model assessment for assessing insulin resistance) are established diagnostic markers of diabetes and insulin resistance respectively, but are relatively expensive. Triglyceride glucose (TyG) index is calculated based on fasting plasma glucose and fasting triglyceride levels which are available as routine laboratory parameters and is inexpensive. This is a preliminary study which aims to compare Triglyceride glucose (TyG) index with HbA1 C as a marker of prediabetes and also with HOMA-IR (Homeostatic model assessment for assessing insulin resistance) as a marker of insulin resistance. Methods: 100 diagnosed cases of prediabetes and 100 age and sex-matched normoglycemic controls were recruited in the study. Fasting plasma glucose, 2-hour OGTT, fasting triglycerides, fasting plasma insulin and HbA1 C were measured. Triglyceride glucose (TyG) index and HOMA-IR (Homeostatic model assessment for assessing insulin resistance) were calculated. Receiver operator curve was plotted and analysed between HbA1 C and Triglyceride glucose (TyG) index. Results: Out of 100 subjects with prediabetes; 53 were female and 47 were male. In this study, there was higher mean Triglyceride glucose (TyG) index (4.942 ± 0.137 vs 4.661 ± 0.173) and HOMA-IR (Homeostatic model assessment for assessing insulin resistance) (2.424 ± 1.045 vs 1.03 ± 0.594) in individuals with prediabetes compared to normoglycemic individuals. The area under curve (AUC) for HbA1C (0.942) was more than Triglyceride glucose (TyG) index (0.898) for the diagnosis of prediabetes. But the difference was not statistically significant with p = 0.06. Conclusions: Triglyceride glucose (TyG) index is comparable to HbA1C as a marker for the diagnosis of prediabetes. Highlights: This was a preliminary study. Triglyceride glucose index as a marker of prediabetes is comparable to HbA1C. Triglyceride glucose index is a known marker of insulin resistance. Triglyceride glucose index is inexpensive and easily available compared to HbA1C.